Biglycan-mediated upregulation of MHC class I expression in HER-2/neu-transformed cells. (3rd April 2018) - Subbarayan, Karthikeyan; Leisz, Sandra; Wickenhauser, Claudia; Bethmann, Daniel; Massa, Chiara; Steven, André; Seliger, Barbara
ABSTRACT: The extracellular matrix protein biglycan (BGN) has oncogenic or tumor suppressive potential depending on the cellular origin. HER-2/neu overexpression in murine fibroblasts and human model systems is inversely correlated with BGN expression. Upon its restoration BGN high HER-2/neu + fibroblasts were less tumorigenic in immune competent mice when compared to BGN low/neg HER-2/neu + cells, which was associated with enhanced immune cell responses and higher frequencies of immune effector cells in tumors and peripheral blood. The increased immunogenicity of BGN high HER-2/neu + fibroblasts appears to be due to upregulated MHC class I surface antigens and reduced expression levels of transforming growth factor (TGF)-β isoforms and the TGF-β receptor 1 suggesting a link between BGN, TGF-β pathway and HER-2/neu-mediated downregulation of MHC class I antigens. Treatment of BGN low/neg HER-2/neu + cells with recombinant BGN or an inhibitor of TGF-β enhanced MHC class I surface antigens in BGN low/neg HER-2/neu-overexpressing murine fibroblasts, which was mediated by a transcriptional upregulation of major MHC class I antigen processing components. Furthermore, BGN expression in HER-2/neu + cells was accompanied by an increased expression of the proteoglycan decorin (DCN). Since recombinant DCN also elevated MHC class I surface expression in BGN low/neg HER-2/neu + cells, both proteoglycans might act synergistically. This was in accordance with in silico analyses of mRNA data obtained from The Cancer Genome Atlas (TCGA) dataset available for breast cancer (BC) patients. Thus, our data provide for the first time evidence that proteoglycan signatures are modulated by HER-2/neu and linked to MHC class I-mediated immune escape associated with an altered TGF-β pathway.